Determinant Price to Earnings Ratio with Total Asset Turnover, Debt to Equity Ratio, Firm Size, and Net Profit Margin - Anggi Sri Aulianti; Devyanthi Syarif (eCo-Fin, 2026)
This study examines the effects of Total Asset Turnover, Debt to Equity Ratio, Firm Size dan Net Profit Margin on Price Earnings Ratio of Indonesian Properties dan Real Estate industry between 2016 and 2024. Employing a quantitative approach that adopts a descriptive and verificative approach, the study looks at 90 financial statements from specific Properties dan Real Estate industry. The correlations between the variables were evaluated using analysis of multiple linear regression, the coefficient of determination test, traditional assumption tests, as well as the product moment correlation coefficient test such as t-tests and F-tests for assessing hypotheses. The data was processed utilizing SPSS 26.0. According to the test findings that are not complete, PER is positively impacted by Total Asset Turnover but DER is negatively impacted. Unfortunately, Firm Size and NPM do not impacted to PER However, the simultaneous test findings show that TATO, DER, Firm Size and NPM taken have a major influence when combined on PER. According to these results, activity TATO, DER, Firm Size and NPM mix are more important factors in determining Price Earnings Ratio in the Properties dan Real Estate industry than short-term.